Corrigendum: Open Social Scholarship Annotated Bibliography. Issue 1 (22nd April 2020) - El Khatib, Randa; Seatter, Lindsey; El Hajj, Tracey; Leibel, Conrad; Arbuckle, Alyssa; Siemens, Ray; Winter, Caroline; ,
Following the publication of our recent article in KULA: Knowledge Creation, Dissemination, and Preservation Studies (https://kula.uvic.ca/articles/10.5334/kula.58/ ), we wish to bring the following corrigendum to your attention.